Occupational Health and Safety Hazards in Machining - Madlova, Danuse; Gebhart, Vlastislav (Manufacturing Technology Journal, 2016)
This paper is focused on occupational health and safety hazards in machining processes. Problem is specified on employs and employers. Occupational health and safety is based on legislative regulations. Safety rules are usually formulated generally. But it is necessary to formulate safety rules more precisely for different production processes and even for different production machines. And this has not been fully satisfactory solved, especially from the point of view of the development of machine tools, their automation and also from the viewpoint of the development of cutting materials. In the paper principal occupational health and safety hazard in machining will be formulated on the base of laws, regulations and personal findings of the paper's authors in different enterprises. As an example safety hazards and safety rules will be in depth formulated for turning. Similar health and safety rules and hazards must be formulated for other cutting processes. But occupational health and safety problems relate not only to persons but also to enterprise economy.
Keywords: Risk; Occupational health and safety; Legislation; Employer; Employee